Margaret Thatcher : the authorized biography/ Charles Moore ; penerjemah, Rini Indardini ; penyunting, Yudi Kurniawan, Nurjannah Intan - MOORE, Charles; Rini Indardini; Yudi Kurniawan; Nurjannah Intan (Bentang, 2014)
xxxv, 1017,[25] hlm.: ilus.; 23 cm